The Wolf at the Door The Menace of Economic Insecurity and How to Fight It - Graetz, Michael J.; Shapiro, Ian (Harvard University Press, 2020)
The acclaimed authors of Death by a Thousand Cuts argue that Americans care less about inequality than about their own insecurity. Michael Graetz and Ian Shapiro propose realistic policies and strategies to make lives and communities more secure. This is an age of crisis. That much we can agree on. But a crisis of what? And how do we get out of it? Many on the right call for tax cuts and deregulation. Others on the left rage against the top 1 percent and demand wholesale economic change. Voices on both sides line up against globalization: restrict trade to protect jobs. In The Wolf at the Door, two leading political analysts argue that these views are badly mistaken. Michael Graetz and Ian Shapiro focus on what really worries people: not what the rich are making but rather their own insecurity and that of people close to them. Americans are concerned about losing what they have, whether jobs, status, or safe communities. They fear the wolf at the door. The solution is not protectionism or class warfare but a return to the hard work of building coalitions around realistic goals and pursuing them doggedly through the political system. This, Graetz and Shapiro explain, is how earlier reformers achieved meaningful changes, from the abolition of the slave trade to civil rights legislation. The authors make substantial recommendations for increasing jobs, improving wages, protecting families suffering from unemployment, and providing better health insurance and child care, and they guide us through the strategies needed to enact change. These are achievable reforms that would make Americans more secure. The Wolf at the Door is one of those rare books that not only diagnose our problems but also show us how we can address them
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2020)
Keywords: POLITICAL SCIENCE / History & Theory; Economic security -- United States; Wirtschaftliche Sicherheit; Wirtschaftspolitik; USA